Design of Road Geometric with AutoCAD® 2D: A Case Wirosari-Ungaran Semarang, Indonesian - Adiputra, Dimas Sukma; Rifai, Andri Irfan; Bhakti, Surya Kencana (DAS Institute, 2022)
The geometric design of the road Wirosari Semarang to Ungaran road section, which is in the city of Semarang, is one of the infrastructures to provide proper road access with optimal travel time. With the division process, the government must provide proper road access with optimal travel time so that the community mobilization process can run smoothly. The research objective is to plan the geometric shape of the road according to the applicable requirements to provide safety and comfort for road users. The Highway Road Geometric Rule method and visualization using AutoCAD® 2D are used. The results of the geometric planning of the road are obtained with a design speed (Vd) of 60 km/hour, a planned road width of 2 x 3.5 meters, and a road alignment with a horizontal curved Spiral Circle Spiral with a radius of 318 m is formed. Meanwhile, the vertical alignment obtained a concave arch type with a length value (L) of 53.28 m